New Triterpenoids from Lansium domesticum Corr. cv kokossan and Their Cytotoxic Activity - Tri Mayanti; Zulfikar; Sarah Fawziah; Al Arofatus Naini; Rani Maharani; Kindi Farabi; Nurlelasari; Muhammad Yusuf; Desi Harneti; Dikdik Kurnia; Unang Supratman (Molecules, 2023)
Lansium domesticum Corr. is a member of the Meliaceae family that is widely spread in tropical and subtropical region of Asia and America. Traditionally, the fruit of this plant has been consumed because of its sweet taste. However, the fruit peels and the seeds of this plant have been rarely utilized. The previous chemical investigation of this plant showed the presence of secondary metabolites with many biological activities, including cytotoxic triterpenoid. Triterpenoids is a class of secondary metabolites which contain thirty carbon atoms in the main skeleton. The high modification of this type of compound, including the ring opening, highly oxygenated carbons, and the degradation of its carbon chain to give the nor-triterpenoid structure, is responsible for its cytotoxic activity. In this paper, we isolated and elucidated the chemical structure of two new onoceranoid triterpenes, kokosanolides E (1) and F (2), from the fruit peels of L. domesticum Corr., along with a new tetranortriterpenoid, kokosanolide G (3), from the seeds of L. domesticum Corr. The structural determination of compounds 1–3 was undertaken through FTIR spectroscopic analysis, 1D and 2D NMR, mass spectrometry, as well as through a comparison of the chemical shifts of the partial structures of compounds 1–3 with the literature data. The cytotoxic properties of compounds 1–3 were tested against MCF-7 breast cancer cells using the MTT assay. Moderate activity was shown by compounds 1 and 3, with IC50 values of 45.90 and 18.41 μg/mL, respectively, while compound 2 showed no activity (IC50 168.20 μg/mL). For the onoceranoid-type triterpene, the high symmetrical structure of compound 1 is presumably the reason for its better cytotoxic activity compared with that of compound 2. Compound 3 showed moderate activity, mainly because of the presence of the furan ring, which, based on the literature, gives better cytotoxic activity in a tetranortriterpenoid-type structure. The findings of three new triterpenoid compounds from L. domesticum indicate the significant value of this plant as a source of new compounds.